2021
DOI: 10.30935/cedtech/9686
|View full text |Cite
|
Sign up to set email alerts
|

Building Mathematics Teachers’ TPACK Through Collaborative Lesson Design Activities

Abstract: Developing teachers' competencies in technology integration has recently been one of the areas of attention in teacher training. This paper presents an investigation of the development of mathematics teachers' technological pedagogical content knowledge (TPACK) through collaborative lesson design activities. The study employed a pre and post-test for non-equivalent groups quasi-experiment with three groups. Participants were secondary school mathematics teachers from Dar es Salaam -Tanzania who responded to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…Moreover, multiple studies have been conducted to determine the effect of cooperation on the knowledge development of pre-service mathematics teachers [18], [38], [39]. This study's results reaffirm the critical nature of teachers' cooperation according to the benefit of the cooperative initiation found in this study.…”
Section: At the Start Of The Program I Had Quite Different Views Abou...supporting
confidence: 78%
“…Moreover, multiple studies have been conducted to determine the effect of cooperation on the knowledge development of pre-service mathematics teachers [18], [38], [39]. This study's results reaffirm the critical nature of teachers' cooperation according to the benefit of the cooperative initiation found in this study.…”
Section: At the Start Of The Program I Had Quite Different Views Abou...supporting
confidence: 78%
“…As Njiku et al (2021) indicated, teachers use technology tools to organize and conduct creative studentcentered activities. For example, the use of a MOOC in the Statistics course facilitated the active role of the participants inside and outside the classroom (You, 2019).…”
Section: Participation Of Studentsmentioning
confidence: 99%
“…McCrae & John (1991) initially developed to provide the basic personality (conscientiousness, openness to experience, neuroticism, extraversion, and agreeableness) as a guide to the comprehensive assessment for education and other organizations. The factors can be an important indicator to support education policy in preparing teachers in the higher teacher (Corcoran & O'Flaherty, 2018;De Jong et al, 2014;Jamil et al, 2012;Njiku et al, 2021;Ozudogru & Ozudogru, 2019). Recently, researchers have paid attention to correlate personality and technological integration (Barnett et al, 2015;Bhagat et al, 2019;A.…”
Section: Introductionmentioning
confidence: 99%